2004
DOI: 10.1152/ajprenal.00181.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of calcium signaling by polycystin-2

Abstract: Autosomal dominant PKD (ADPKD) is a common lethal genetic disorder characterized by progressive development of fluid-filled cysts in the kidney and other target organs. ADPKD is caused by mutations in the PKD1 and PKD2 genes, encoding the transmembrane proteins polycystin-1 (PC1) and polycystin-2 (PC2), respectively. Although the function and putative interacting ligands of PC1 are largely unknown, recent evidence indicates that PC2 behaves as a TRP-type Ca 2ϩ -permeable nonselective cation channel. The PC2 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 157 publications
(264 reference statements)
0
49
1
Order By: Relevance
“…Subsequently, single channel studies in placental preparations [31], heterologously expressed PKD2 in Xenopus oocytes [32] and HEK293 cells [33], and in vitro translated purified PKD2 in cell-free systems [31] further characterized PKD2 activity. Despite subtle disparities among these studies [34], it was concluded that PKD2 could form a functional channel in the plasma membrane with constitutive activity upon overexpression. It allowed non-selective passing of cations, with slightly higher selectivity for Ca 2+ over Na + and K + , but higher conductance in K + [34].…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, single channel studies in placental preparations [31], heterologously expressed PKD2 in Xenopus oocytes [32] and HEK293 cells [33], and in vitro translated purified PKD2 in cell-free systems [31] further characterized PKD2 activity. Despite subtle disparities among these studies [34], it was concluded that PKD2 could form a functional channel in the plasma membrane with constitutive activity upon overexpression. It allowed non-selective passing of cations, with slightly higher selectivity for Ca 2+ over Na + and K + , but higher conductance in K + [34].…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
“…Despite subtle disparities among these studies [34], it was concluded that PKD2 could form a functional channel in the plasma membrane with constitutive activity upon overexpression. It allowed non-selective passing of cations, with slightly higher selectivity for Ca 2+ over Na + and K + , but higher conductance in K + [34]. However, the high single channel conductance (100-200 pS) [24,31,35] in combination with the relatively high open probability (~20-40%) [24,31,35] did not correlate well with the moderate amplitude of whole cell currents (several hundreds pA at -100 mV) in cells overexpressing PKD2 [35,36].…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
“…In this case, an increase in the hydrodynamic torque on the microvilli is believed to increase the efficiency of absorption of Na + to maintain glomerulotubular balance [56]. Kidney epithelial cells are appear to be able to sense flow via their primary cilia, deformation of which causes increases in intracellular Ca 2+ [57].…”
Section: Espins In the Microvillar Processes Of Other Sensory Cellsmentioning
confidence: 99%
“…According to primary sequence similarity, the members of the TRP gene family are classified into six subfamilies: TRPCs (seven canonical or classical TRPs), TRPVs (six vanilloid receptor and related proteins), TRPMs (eight TRP proteins homologous to the first cloned mammalian subfamily member, melastatin; Montell et al 2002a,b;Clapham et al 2003), TRPA (a single gene is present in mammalian genomes, ANKTM1; Tominaga and Caterina 2004), and two groups of more distantly related proteins, TRPMLs (three proteins defined by the initially discovered gene mucolipin 1; Slaugenhaupt 2002) and TRPPs (polycystic kidney disease 2 related proteins; Cantiello 2004). The current manuscript focuses on recent progress made in the field of TRPM cation channels.…”
Section: Introductionmentioning
confidence: 99%